2020
DOI: 10.3390/molecules25010191
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Moringa oleifera Lam. Leaves Inhibit the Pro-Inflammatory Mediators in Lipopolysaccharide-Induced Human Monocyte-Derived Macrophages

Abstract: Moringa oleifera (MO) is an important plant for traditional medicine. The present study aimed to identify the MO active phytochemical compounds for their ability against inflamed macrophages. An ethyl acetate extract fraction of MO was fractionation by flash column chromatography. Human macrophages were stimulated by Lipopolysaccharide and then treated with fractions of MO to examine their anti-inflammatory activity and cellular mechanism. The active fractions were analyzed by liquid chromatography with electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…MO presents a wide variety of biological activities evidenced in in vitro experiments, showing potent anti-oxidative, analgesic, cytoprotective, anti-ulcer, anti-hypertensive and immunmodulatory actions as well as an inhibitory effect on proinflammatory mediators such as iNOS, COX-2, PGE-2, TNF-α, IL-1β and IL-6 [2,17,[20][21][22][23]. It is a popular medicine used in Asia and Africa for multiple purposes, ascribed to the various parts of the plant, which, in addition, are used in many different ways [7].…”
Section: Introductionmentioning
confidence: 99%
“…MO presents a wide variety of biological activities evidenced in in vitro experiments, showing potent anti-oxidative, analgesic, cytoprotective, anti-ulcer, anti-hypertensive and immunmodulatory actions as well as an inhibitory effect on proinflammatory mediators such as iNOS, COX-2, PGE-2, TNF-α, IL-1β and IL-6 [2,17,[20][21][22][23]. It is a popular medicine used in Asia and Africa for multiple purposes, ascribed to the various parts of the plant, which, in addition, are used in many different ways [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our results reveal a decrease in mRNA (Figure 5c,d) and protein levels ( Figure 6a,c) of TNF-α and IL1β markers in DM preconditioned hADMSCs. Similar down regulation at mRNA and protein level of IL1β beta and TNF-α has recently been reported in Lipopolysaccharide-Induced Human Monocyte-Derived Macrophages [75]. On the other hand, matrix metalloproteinase-13 (MMP-13) is a metalloproteinase enzyme that is involved in the degradation of extracellular matrix [76,77].…”
Section: Discussionmentioning
confidence: 52%
“…There is a great interest in the discovery of biologically active natural products due to their activities with relatively low toxicity as compared to other modalities such as synthetic chemicals [ 10 ]. Numerous studies have shown that natural products are developed as beneficial dietary supplements for health and therapeutic agents against disease [ 25 ]. Lichen is a unique organism that produces biologically active secondary metabolites with various pharmacological effects including antioxidant, anti-cancer [ 17 ] and anti-viral effects [ 16 ].…”
Section: Discussionmentioning
confidence: 99%